Nevada exploratory Alzheimer's disease research center: Advancing dementia care in rural communities. (31st December 2021) - Sabbagh, Marwan Noel; Ritter, Aaron; Cummings, Jeffrey L.; Wint, Dylan; Decourt, Boris; Wong, Christina G; Caldwell, Jessica ZK; Kinney, Jefferson W; Carriere, Lucille; Cordes, Dietmar; Fulkerson, Nadia; Almoraissi, Abla; et al.
Abstract: Background: People with MCI and AD living in rural areas represent an understudied and underserved population in the broader AD landscape. Very little works have been done on rural cohorts by NIA‐designated Alzheimer's Disease Research Centers (ADRCs) in the past. The Nevada Exploratory ADRC (NVeADRC) is specifically set to study AD and related dementias in rural individuals, and to systematically generate novel data on the clinical features of AD, clinical outcomes, and social determinants of health. Method: The leading scientific objectives of the NVeADRC are to: 1) understand the occurrence of AD and optimize treatment in underserved rural settings; 2) examine risk factors associated with the development of AD in rural areas; and 3) evaluate the trajectories and progression of AD in rural versus urban communities. The NVeADRC will deploy a top‐down strategy to: 1) establish a network of stakeholders and medical partners to increase awareness of dementia in rural communities and enroll rural participants in our research cohort; 2) develop a research enterprise for longitudinal studies on dementia in rural populations; 3) progressively implement a research infrastructure rooted in technology to facilitate standardized clinical data collection from patients in rural areas. Result: The data collected will be part of the National Alzheimer's Coordinating Center (NACC) and shared with the larger scientific community to ultimately to improve healthcare for patients in rural areas. Target recruitment for the NVeADRC include 20 Mild Cognitive Impairment, 40 dementia due to Alzheimer's disease and 40 cognitively normal subjects. In addition to the Uniform Data Set 3.0, we intend to collect volumetric MRI, biofluids (blood, saliva, and cerebrospinal fluid), as well as, a series of both static and dynamic social determinants of health on study subjects and their partners. All participants will be followed to voluntary withdrawal or autopsy. Conclusion: The NVeADRC represents a unique, high impact entity within the ADRC network, and will generate high‐quality biomedical data that advance AD/ADRD research on individuals living in underserved rural communities. As we grow our project, we intend to share biospecimens and data with the scientific community.